The more things change, the more they stay the same, or do they? Revisiting classroom interaction approaches and their effects on quantity and characteristics of language production. (20th January 2015) - Unknown
Abstract : This study investigated the quantity and characteristics of student language production, discourse functions, and morphosyntactic features in three different discourse settings – face-to-face (F2F), lab-setting chatroom interactions (Lab), and any place/ any device chatroom interactions (APAD). Discourse was examined through the replication and extension of Richard Kern's (1995) study. Similarities in findings between the two studies included a continuation of incomplete, and short sentence lengths among F2F students, an absence of F2F greetings, and a higher rate of assertions, verb tenses, and simple sentences in the Lab setting. Differences included a higher rate of F2F turns in the current study, an absence of greetings in the lab setting, and a greater number of commands among F2F participants. Findings underscored what Kern previously asserted: that F2F and chatroom settings tend to encourage and support slightly different goals associated with language discourse. Kern stated that more sophisticated conversation occurred in the chatroom setting. Current findings concurred but furthered that more conversational interaction took place within the F2F discourse setting due to a greater number of commands, turns, and incomplete sentences. Similarly, F2F students experienced greater input due to the increase of words heard, questions asked, and commands made.